Snapshot of Medicine Inventory Management in Hospitals: Case Study of Low Back Pain - Wonsu, Andi Selvi Kartini; Muttaqim, Muttaqim; Samboteng, Lukman; Imbaruddin, Amir; Widyawaty, Andi (Universitas Negeri Makassar, 2025)
Management of medicines in hospitals is the main work of pharmacy that ensures their efficient, effective, and sustainable use. This study aims to explore the medicine management system implemented in hospitals, with a case study on medicine management for patients with low back pain. The case study approach was used to obtain primary data through in-depth interviews with pharmacy staff and secondary data from documents related to medicine inventory. The results of the study indicate that the management of medicines for back pain faces challenges in the form of demand uncertainty, inter-unit coordination, and limitations of information technology systems. The strategies implemented include the use of the Just-In-Time method to minimize waste, regular stock monitoring, and data-based evaluation of medicine use. However, this study also found that limited human resources and budget are often the main obstacles in optimizing inventory management. Therefore, a systematic and integrated technology-based approach is needed to improve the efficiency of medicine management in hospitals, especially in handling cases of low back pain.